The level of readiness and strategy of Jambi city to become an Islamic smart city in supporting Islamic smart tourism - Sigit Indrawijaya; Nurida Isnaeni; Dahmiri Dahmiri (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The purpose of this study was to determine the readiness of Jambi City to become an Islamic Smart City closely related to Islamic Smart Tourism and formulate a strategy through a SWOT analysis for Jambi City to become an Islamic Smart City. This research uses mixed methods. The sample of this study amounted to 30 respondents who are managers of tourist attraction objects in Jambi City. Data collection techniques in this study are observation, questionnaires/questionnaires, interviews, and documentation studies. The analysis technique in this study uses scoring analysis and for strategic conclusions using SWOT analysis. The results of this study can be concluded that the level of readiness of the City of Jambi in Islamic Smart Tourism is at a score of 7, which means the category is somewhat ready. Based on the SWOT analysis results, there are strengths, weaknesses, opportunities, and threats for Jambi City to become an Islamic Smart City in supporting Islamic Smart Tourists.